8 - ‘Makererization’: Politics, Leadership and Management at the University of Botswana from 2011-2017 - Makgala, Christian John (Journal of Higher Education in Africa, 2022)
I recently visited a friend in Soweto to pay my condolences after his wife died. While I was still in the process of greeting my bereaved friend, he said to me, “Thabo, I understand that you are the new Vice Chancellor for the University of Botswana, my condolences to you”!Professor Thabo FakoThis article examines an aspect of higher education leadership and university management through a critical appraisal of the leadership style and tenure of Professor Thabo Fako as Vice Chancellor (VC) of the University of Botswana (UB) from 2011 to 2017 and his attempts to dismantle the reforms of his predecessor. It addresses the important role played by the intersection between character, political strategy and administrative leadership in higher education reform. The article thus examines the manner in which these concurrently affect democratic and good corporate governance at university institutions, and as well the risks they pose in engendering widespread fear and institutional paralysis. It is written against the backdrop of a paper in 2004 by this VC castigating organizational restructuring undertaken by UB during that period. The article argues that state intervention in the selection and appointment of university management stalled reform and introduced a leader rendered paranoid by the selection process. ‘Makererization’ is used here to refer to the marginalization of UB by government through reduced funding and the VC’s persecution of university staff and students.